CTLA4Ig Improves Murine iTreg Induction via TGFβ and Suppressor Function In Vitro - Nina Pilat; Benedikt Mahr; Martina Gattringer; Ulrike Baranyi; Thomas Wekerle (Journal of Immunology Research)
Blockade of the CD28:CD80/86 costimulatory pathway has been shown to be potent in blocking T cell activation in vitro and in vivo. The costimulation blocker CTLA4Ig has been approved for the treatment of autoimmune diseases and transplant rejection. The therapeutic application of regulatory T cells (Tregs) has recently gained much attention for its potential of improving allograft survival. However, neither costimulation blockade with CTLA4Ig nor Treg therapy induces robust tolerance on its own. Combining CTLA4Ig with Treg therapy would be an attractive approach for minimizing immunosuppression or for possibly achieving tolerance. However, since the CD28 pathway is more complex than initially thought, the question arose whether blocking CD80/86 would inadvertently impact immunological tolerance by interfering with Treg generation and function. We therefore wanted to investigate the compatibility of CTLA4Ig with regulatory T cells by evaluating direct effects of CTLA4Ig on murine Treg generation and function in vitro. For generation of polyclonal-induced Tregs, we utilized an APC-free in vitro system and added titrated doses of CTLA4Ig at different time points. Phenotypical characterization by flow cytometry and functional characterization in suppressor assays did not reveal negative effects by CTLA4Ig. The costimulation blocker CTLA4Ig does not impair but rather improves murine iTreg generation and suppressor function in vitro.